2021
DOI: 10.1186/s12912-021-00671-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a ‘do not interrupt’ vest intervention to reduce medication errors during medication administration: a multicenter cluster randomized controlled trial

Abstract: Background The use of a ‘do not interrupt’ vest during medication administration rounds is recommended but there have been no controlled randomized studies to evaluate its impact on reducing administration errors. We aimed to evaluate the impact of wearing such a vest on reducing such errors. The secondary objectives were to evaluate the types and potential clinical impact of errors, the association between errors and several risk factors (such as interruptions), and nurses’ experiences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
2
10
0
2
Order By: Relevance
“…The odds of medication administration errors were higher among nurses who faced interruptions during medication administration compared with nurses who did not face interruptions, which is in agreement with findings of other studies. [42][43][44] Studies revealed that work interruptions during medication administration rounds are thought to be a prominent factor in medication errors that account for up to 43% of medication errors. 43 45 Nurses must remain attentive and focused when performing activities that require concentration to avoid distractions and errors.…”
Section: Discussionmentioning
confidence: 99%
“…The odds of medication administration errors were higher among nurses who faced interruptions during medication administration compared with nurses who did not face interruptions, which is in agreement with findings of other studies. [42][43][44] Studies revealed that work interruptions during medication administration rounds are thought to be a prominent factor in medication errors that account for up to 43% of medication errors. 43 45 Nurses must remain attentive and focused when performing activities that require concentration to avoid distractions and errors.…”
Section: Discussionmentioning
confidence: 99%
“…Solberg et al (2021) also cited Brady et al's (2009) study and used a cross‐sectional study investigation of drug modification. Furthermore, based on Brady et al's (2009) study, Berdot et al (2021) used a multicentre cluster randomized controlled trial to investigate reducing medication errors during medication administration. Speare et al (2021) then followed the study of Berdot et al (2021) to explore medication errors and medication administration related to nursing competence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, based on Brady et al's (2009) study, Berdot et al (2021) used a multicentre cluster randomized controlled trial to investigate reducing medication errors during medication administration. Speare et al (2021) then followed the study of Berdot et al (2021) to explore medication errors and medication administration related to nursing competence. These papers can be used as a reference for researchers to track or attempt studies in the same direction.…”
Section: Discussionmentioning
confidence: 99%
“…In some interruption-prone environments, people have tried a variety of methods to reduce interruptions. For instance, in hospitals, people tried designating "interruptionfree" zones or using "do not interrupt" jackets [3,5]. However, it is unclear whether such methods will be feasible or effective long term [8].…”
Section: Key Challengesmentioning
confidence: 99%